Characterization of histone acetyltransferases and deacetylases and their roles in response to dehydration stress in Pyropia yezoensis (Rhodophyta) - Zhang, Zehao; Qian, Huijuan; Wang, Zhongshi; Pang, Ying; Guan, Xiaowei; Poetsch, Ansgar; Wang, Dongmei (Frontiers in Plant Science, 2023)
Histone acetylation is one of the most pivotal epigenetic mechanisms in eukaryotes and has been tightly linked to the regulation of various genes controlling growth, development and response to environmental stresses in both animals and plants. Till date, the association of histone acetylation to dehydration stress in red algae and genes encoding the enzymes responsible for histone acetylation: histone acetyltransferases (HATs) or histone deacetylases (HDACs), remains largely unknown. In this study, in silico analysis of the red seaweed Pyropia yezoensis identified 6 HAT genes and 10 HDAC genes. These genes displayed good synteny in genome loci with their Pyropia haitanensis orthologs except for a putative gene duplication event in HDAC and a loss of one HAT gene in P. yezoensis. According to the conserved domains and phylogenetic analysis, they encoded three GCNA5-, one TAFII250- and one MYST-HAT, as well as five HDA1-and five SIRT-HDACs. The sirtuin-domain of Py06502 harbored a 100 aa insert and interestingly, this insertion was specifically observed in Bangiales species. Two nuclear-localized HATs were transcriptionally up-regulated at the early stage of dehydration and so were two nuclear HDA1s when moderate dehydration started, suggesting their potential roles in modulating downstream gene expression to facilitate dehydration adaptation by changing histone acetylation patterns on relevant regulatory elements. This was experimentally confirmed by the increased decline in photosynthesis efficiency during dehydration when HAT and HDAC activities were inhibited by SAHA and MB-3, respectively. Transcriptional patterns of multiple dehydration-responsive genes after water loss were strongly affected by MB-3 or SAHA treatment. This study provides the first insight into the regulation and function of HAT/HDAC during stress adaptation in red algae.